Online games for learning Lewis Structure / Wan Elina Faradilla Wan Khalid ... [et al.] - Wan Khalid, Wan Elina Faradilla; Syed Ahmad, Tuan Sarifah Aini; Jani, Nor Akmalazura; Saat, Rohaiza; Mohd Nor, Nurazira (2021)
The application of online games has become prevalent in learning various courses including Chemistry. There are various online games for learning Chemistry which are available ubiquitously on many free online platforms. However, most of the games are developed by using applications which provide specific templates. The applications also only allow limited modifications in terms of game design which involves multimedia and gamification elements. Therefore, the Chemistry online game called Play Chemistry: Lewis Structure is developed by using the application called Scratch which allows unlimited game design based on the creativity of the developers. The topic, Lewis Structure, is selected due to the reason that the topic is challenging to be learnt by the students at the tertiary level. This paper aims to describe the development of a series of Chemistry online games called Play Chemistry: Lewis Structure. The series contains three games for three molecules namely tetrachloromethane (CCl4), methane (CH4) and water (H2O). The games are developed for tertiary students at the diploma/degree level. The instructional design model applied for the design and development of the games is the ADDIE Model. The game adopts structural gamification by applying selected gamification elements such as score, praise feedback, explanatory feedback, verification feedback, and lives. The games are embedded on Google Site (https://sites.google.com/view/lewis-structure/home) for the students’ easy access. The three molecules are considered easy molecules. Therefore, future work will focus on more difficult molecules.